Funções sigmoidais aplicadas na determinação da atividade metanogênica específica - AME - Silva, Helenice de Oliveira Florentino [UNESP]; Biscaro, Adriana de Fátima Vilela [UNESP]; Passos, José Raimundo de Souza [UNESP] (My University, 2010)
The success of any anaerobic process basically depends on maintaining, in the reactors, a biomass with elevated microbiological activity which is resistant to shocks. For this biomass to be maintained and monitored, techniques need to be developed to evaluate microbial activity. Several methods have already been developed starting with Specific Methanogenic Activity (SMA). Tests were proposed to evaluate the capacity of methanogenic bacteria to convert organic substrate into methane and carbon dioxide. However the importance of this type of test is its ability to evaluate and classify the potential of the biomass in converting soluble substrates into biogas. The objective of this study is to demonstrate the use of mathematical tools that can help SMA evaluation, using sigmoidal models. It is easy to determine inflection point in sigmoidal curves, and from this estimate the temperature where maximum variation rate of methane production; this facilitates SME evaluation and helps resolve imprecision problems found in traditional methods.

O sucesso de um processo anaeróbio em reatores, depende fundamentalmente da manutenção de uma biomassa com elevada atividade microbiológica e resistente a choques. Para que essa biomassa possa ser preservada e monitorada, foram desenvolvidas técnicas para a avaliação da atividade microbiana, como por exemplo, o teste da Atividade Metanogênica Específica (AME), cujo propósito consiste em avaliar a capacidade das bactérias metanogênicas em converter substrato orgânico em metano e gás carbônico. O objetivo deste trabalho, para auxiliar o teste da AME, é determinar a taxa máxima de variação de produção de metano através da estimativa do ponto de inflexão de modelos de regressão não-linear ajustados aos dados observados, pelo método dos mínimos quadrados.
Sigmoidal functions applied in the determination of specific methanogenic activity - SMA
Keywords: Anaerobic digestion; Mathematical model; Potential of the biomass; Digestão anaeróbia; Modelagem matemática; Potencial da biomassa